The role of tax incentives, their considerations and effects in promoting investments and attracting investors in the Kingdom - Sarah Mohammed Al-Duwaish; Shams Mubarak Al-Qahtani; Lina Tariq Al-Shaya; Manal Jaber Hazzazi; Munira Abdulrahman Al-Khunaifer; Rania Aboud Ahmed Bin Madi (International Journal of Law Research and Studies, 2025)
This research aims to study the role of tax incentives, their considerations, and impacts on promoting investments and attracting investors in the Kingdom of Saudi Arabia. It explores how tax incentives contribute to attracting both domestic and foreign investments, along with an analysis of the effectiveness of current tax policies and their impact on the growth of the local economy. The research also seeks to identify the challenges associated with the implementation of these incentives and ways to overcome them, providing practical recommendations to improve tax policies in alignment with the goals of Vision 2030. The research problem arises from the desire to understand the effectiveness of tax incentives in boosting investments in the Kingdom, assess whether these incentives meet investor needs, and evaluate their role in fostering economic growth. The study also aims to explore the barriers and challenges that may affect the effectiveness of these incentives and examine the Kingdom’s ability to learn from successful international experiences in this field. The research proposes a set of recommendations, including the continued provision of tax incentives in general, while directing them to support sectors that contribute to achieving Vision 2030, such as innovation and technology, energy, tourism, and the industrial sectors. It also recommends developing regular monitoring and evaluation mechanisms for tax incentive programs to ensure that the intended economic and social goals are achieved, with a focus on directing incentives toward investments that promote job localization and support innovation. Among the recommendations, the study emphasizes the preparation of a simplified guide outlining the main tax incentives and benefits offered to companies, to be distributed to major companies to encourage investment in the Kingdom. Additionally, the research suggests that further studies be conducted on the obstacles to foreign investment and ways to address them. It also recommends launching an international promotional campaign to inform foreign investors about the opportunities available in the Kingdom, including tax incentives, and providing technical and advisory support to help foreign investors understand the tax system and benefit from the available incentives.
Keywords: Tax Incentives; Investment; Investors; Saudi Arabia